Is It Time to Include CT "Reverse Halo Sign" and qPCR Targeting Mucorales in Serum to EORTC-MSG Criteria for the Diagnosis of Pulmonary Mucormycosis in Leukemia Patients?. (8th November 2016) - Caillot, Denis; Valot, Stéphane; Lafon, Ingrid; Basmaciyan, Louise; Chretien, Marie Lorraine; Sautour, Marc; Millon, Laurence; Legouge, Caroline; Payssot, Alexandre; Dalle, Frédéric
Abstract: In 23 leukemia patients with proven (n = 17) or possible (n = 6) pulmonary mucormycosis (PM), the presence of reversed halo sign on computed tomography was strongly associated with the positivity of quantitative polymerase chain reaction assays targeting Mucorales in the serum, confirming the value of these two tools for the diagnosis of PM in this setting.